1997
DOI: 10.1104/pp.114.2.445
|View full text |Cite
|
Sign up to set email alerts
|

Putrescine Aminopropyltransferase Is Responsible for Biosynthesis of Spermidine, Spermine, and Multiple Uncommon Polyamines in Osmotic Stress-Tolerant Alfalfa

Abstract: The biosynthesis of polyamines from the diamine putrescine is not fully understood in higher plants. A putrescine aminopropyltransferase (PAPT) enzyme activity was characterized in alfalfa (Medicago sativa L.). This enzyme activity was highly specific for putrescine as the initial substrate and did not recognize another common diamine, 1,3-diaminopropane, or higher-molecular-weight polyamines such as spermidine and spermine as alternative initial substrates. The enzyme activity was inhibited by a general inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…It has been suggested that plant SPDS may occur in the form of a multienzyme complex (Bagga et al, 1997). Thus, characterization of SPDS in crude alfalfa enzyme extracts showed that although alfalfa SPDS was highly specific for putrescine as the initial substrate, extended enzymatic reaction produced, besides spermidine, spermine and several uncommon polyamines (Bagga et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that plant SPDS may occur in the form of a multienzyme complex (Bagga et al, 1997). Thus, characterization of SPDS in crude alfalfa enzyme extracts showed that although alfalfa SPDS was highly specific for putrescine as the initial substrate, extended enzymatic reaction produced, besides spermidine, spermine and several uncommon polyamines (Bagga et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It also prevents the loss or dilution of substrate by diffusion and protects chemically labile intermediates (Ovadi and Srere, 2000). An early report on the purification of SPDS from alfalfa suggested that this enzyme might produce different polyamines, including spermine and other uncommon compounds, in addition to spermidine (Bagga et al, 1997). The fact that the different products were produced at different rates indicated that these reactions cannot be catalyzed by a single SPDS enzyme; most likely, an enzyme complex is required.…”
Section: Introductionmentioning
confidence: 99%
“…2) as a co-product of the oxidation of Spd (47). However, the alfalfa aminopropyltransferase did not recognize Dap as a substrate, although it was able to produce Spd, Spm, and Tspm from Put (48). Production of Nspd in eukaryotes therefore was a mystery until very recently, when it was shown that a plant polyamine oxidase produces Nspd as a catabolic product from Tspm (49).…”
Section: Biosynthetic Diversification Via Endosymbiotic and Horizontamentioning
confidence: 99%
“…Furthermore, uncommon polyamines, such as norspermidine (Nor-Spd), homospermidine, norspermine (Nor-Spm), homospermine, thermospermine, caldopentamine, caldohexamine, homocaldopentamine, and homocaldohexamine, are abundant in the extreme thermophilic bacterium Thermus thermophilus and have also been detected in bacteria, algae, fungi, animals, and higher plants (Cohen, 1998). In plants, a putative role for these molecules in growth, differentiation, and stress tolerance has been hypothesized (RodriguezGaray et al, 1989;Bagga et al, 1997;Koc et al, 1998).…”
mentioning
confidence: 99%